Systematic Literature Review the Development of Enterprise Risk Management - Mona Nur Adhillah; Mutiara Syalwa; Putri Meilanda; Rela Sari (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2025)
Enterprise Risk Management (ERM) strengthens governance and organizational resilience amid business uncertainty. The complex, collective decision-making process, influenced by many internal and external factors, demands an ERM approach that is more than just technical or economic. A Systematic Literature Review (SLR) of 25 articles (2016–2025) from Emerald, Taylor & Francis, MDPI, and Google Scholar shows ERM positively influences firm performance and value, especially when integrated with ESG, good governance, and organizational knowledge. The research spans several Asian and European countries, including Malaysia and Indonesia, and covers diverse sectors. ERM effectiveness depends on firm size, ownership, and industry. Today, ERM is seen as a dynamic strategic capability, although implementation challenges remain, particularly for SMEs and family businesses. The study also highlights conceptual trends, methodological diversity, and future research directions.